ANALISIS PENGARUH MOTIVASI, DISIPLIN DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PT. PILAR KEKAR PLASINDO SURAKARTA - Budiwinarto, Kim; Firdausi, Rifai Nur (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2023)
This study aims to analyze the effect of motivation, discipline and job training on employee performance at PT. Pilar Kekar Plasindo Surakarta. This research method uses a quantitative approach by collecting data through questionnaires distributed to employees of PT. Pilar Kekar Plasindo Surakarta. The research sample consisted of 65 respondents who were taken from all employees in the company. The collected data were analyzed using multiple linear regression techniques to test the research hypothesis. The results of the analysis show that motivation has a positive and significant effect on employee performance. In addition, work discipline also influences employee performance positively and significantly. Furthermore, job training also has a positive and significant impact on employee performance. Furthermore, the results of this study make an important contribution to PT. Pilar Kekar Plasindo Surakarta in developing an effective human resource management strategy. Companies can strengthen motivation, improve employee work discipline, and develop good job training to achieve better overall performance.